2010
DOI: 10.1016/j.scr.2009.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sonic hedgehog signaling and the expression of its components in human embryonic stem cells

Abstract: Human embryonic stem cells (hESC) are characterized by their ability to self-renew and differentiate into all cell types of the body, making them a valuable resource for regenerative medicine. Yet, the molecular mechanisms by which hESC retain their capacity for self-renewal and differentiation remain unclear. The Hedgehog signaling pathway plays a pivotal role in organogenesis and differentiation during development, and is also involved in the proliferation and cell-fate specification of neural stem cells and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
33
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 48 publications
8
33
0
Order By: Relevance
“…Activation of the SHH pathway drives the development of neural crest stem cells and the sympathetic nervous system (Wu et al, 2010). Thus, it is not surprising that dysregulation of the SHH pathway correlates with the central nervous system tumorigenesis (Dahmane et al, 2001).…”
Section: Gscs and Their Characteristicsmentioning
confidence: 99%
“…Activation of the SHH pathway drives the development of neural crest stem cells and the sympathetic nervous system (Wu et al, 2010). Thus, it is not surprising that dysregulation of the SHH pathway correlates with the central nervous system tumorigenesis (Dahmane et al, 2001).…”
Section: Gscs and Their Characteristicsmentioning
confidence: 99%
“…In pancreatic adenocarcinoma of both acinar and ductal origins most pathways, including Sonic Hedgehog (Shh), Wnt, Notch and transforming growth factor β (TGFβ) signaling, have been shown to be dysregulated (Bailey and Leach, 2012). During embryonic development, Shh plays a major role in stem-cell proliferation (Wu et al, 2010); the Wnt pathway is involved in cell proliferation and differentiation (Yang, 2012); Notch is responsible for stem-cell maintenance (Kwon et al, 2012); and TGFβ controls cell and tissue homeostasis, favoring cell apoptosis by cross-talking with other pathways such as p53 (Elston and Inman, 2012). TGFβ is also involved in tissue morphogenesis, in cooperation with Wnt pathway, by controlling epithelial-to-mesenchymal transition (EMT) and cell migration (Jing et al, 2011; Zhou et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In the squamous cell carcinoma of the lungs, protein kinase CΙ (PKCΙ) was found to phosphorylate Sox2 and recruit it to the Hh acyltransferase ( HHAT ) promoter for Hh ligand production and maintenance of a stem-like phenotype [349]. Although study showed minimal role of SHh pathway in maintaining pluripotency and regulating the proliferation of undifferentiated hESCs, Gli-responsive luciferase assay and target genes Ptch1 and Gli1 expression during differentiation with retinoic acid revealed that the SHh signaling pathway is highly activated [93]. Besides, addition of exogenous SHh to differentiating hESC as embryoid bodies increases the expression of neuroectodermal markers Nestin, SOX1, MAP2, MSI1, and MSX1, suggesting that SHh signaling is important during hESC differentiation toward the neuroectodermal lineage [93].…”
Section: Specific Protein Kinases and Associated Signaling Pathwaymentioning
confidence: 99%
“…Although study showed minimal role of SHh pathway in maintaining pluripotency and regulating the proliferation of undifferentiated hESCs, Gli-responsive luciferase assay and target genes Ptch1 and Gli1 expression during differentiation with retinoic acid revealed that the SHh signaling pathway is highly activated [93]. Besides, addition of exogenous SHh to differentiating hESC as embryoid bodies increases the expression of neuroectodermal markers Nestin, SOX1, MAP2, MSI1, and MSX1, suggesting that SHh signaling is important during hESC differentiation toward the neuroectodermal lineage [93]. This comes in line with a previous report [350] that implicates the Hh pathway in a core developmental signaling network repressive for pluripotency, as revealed by a ChIP-chip dataset that regulates Yamanaka factors in iPSCs.…”
Section: Specific Protein Kinases and Associated Signaling Pathwaymentioning
confidence: 99%
See 1 more Smart Citation